Caring for Serious Mental Illness Patients with High Risk of Committing Violence by Using Case Management: A Case Study - Wongpanarak, Dr. Narisa; Sermsai, Phasit (Academic Psychiatry and Psychology Journal, 2024)
Case management is a collaborative process for quality services to address a patient’s and family’s needs in a cost-effective and safe manner to promote optimal outcomes. The patient in this study poses a high risk for violence and lacks a direct caregiver. Community members are afraid of the patient’s violent behaviors, and the hospital responsible for caring for the patient is a community hospital without a specialist in psychiatry. This article aims to explain the case management process using clinical resource management models in caring for patients with complex problems in community hospitals. The community hospital has limited potential to provide total and holistic care by experts and network associates, which affects other departments within the same context. The integration of SMI-V into the care process results in ongoing care at community hospitals, with network associates involved in caring, planning, and system management. As a result, the patient in this case had no hospital readmissions within two years, and there were no recurrences of violence in the community. The patient, family, and the healthcare provider team were all satisfied with the case management process.